Acoustooptic conversion of te and tm modes in a diffusive planar waveguide - SZUSTAKOWSKI, Mieczysław; ŚWIETLICKI, Bogusław (Archives of Acoustics, 1982)
This paper gives the results of calculations of the accoustooptic effect in a. planar graded index waveguide obtained from the diffusion of titanium to a Y-cut LiNbO3. The effect of TE and TM modes are considered. The effectiveness of diffraction (TE_m -> TE_m -> TM_m -> TM_m) and conversion (TE_m -> TE_n, TM_m -> TM_n, TE_m ->TM_Lm) of modes, depending on the acoustic power is investigated. Calculations are carried out for acoustic wave of 360 MHz frequency.